Różnica między ryzykiem a niepewnością i ich wpływ na sytuację decyzyjną podmiotu - Kuśmierczyk, Paweł (The Difference between Risk and Uncertainty and their Impact on the Agent's Decision Situation, 2005)
The decisions made by economic agents under the conditions of incomplete Information are most often divided into decisions made under risk and under uncertainty. Risk is to be understood as a situation when the objective probabilities of future events are being given, opposed to the uncertainty when such Information is not known. This classification proposed by Knight in 1921 practically lost its significance when Savage suggested that under conditions of uncertainty agents behave as if they based their decisions on the complete system of subjective probabilities. However, later findings, started with the experiments described by Ellsberg, proved that behaviour under uncertainty differs clearly from the predictions of expected utility model. It turned out that under uncertainty subjective probabilities system that agents use is incomplete and indistinct which has significant influence on agents' decisions. Moreover, as practically no economic decisions are being made under risk and almost all are being made under uncertainty these results imply that expected utility model has to be deeply modified in order to describe more accurately and predict more successfully decisions made under the conditions of incomplete information.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (11); 2005; nr 1077, s. 9-20